Analyzing Current Approaches to Assessing the Quality of Software Products - A. A. Drozhkin (Вестник Российского экономического университета имени Г. В. Плеханова)
Information technologies are the fastest developing industry today both in global economy and economy of Russia. Serious attention is paid to methodological aspects of quality management. Raising quality of software products is an objective of implementing the national project ‘Digital Economy of the Russian Federation’. Processes and stages of software development are modified with regard to new requirements to end product in accordance with adopted home standards. Thus the goal of improving the quality of software products is really topical. The quality of software product is influenced by various determinate and casual external and internal factors. Home experience of managing software quality refers to both western experience and works by Russian scientists, such as G. G. Azgal’dov, Yu. P. Adler, I. G. Venetskiy, V. V. Lipaev, S. D. Il’enkova, I. F. Shishkin, P. L. Chenyshev, V. M. Mishin. The article studies methods of managing software product quality that are used in home IT companies and carries out their comparative analysis. The author formulated proposals aiming at identification of drawbacks by using methods of cognitive modeling.